2012
DOI: 10.1186/bcr3121
|View full text |Cite
|
Sign up to set email alerts
|

Common variants at 12p11, 12q24, 9p21, 9q31.2 and in ZNF365 are associated with breast cancer risk for BRCA1 and/or BRCA2mutation carriers

Abstract: IntroductionSeveral common alleles have been shown to be associated with breast and/or ovarian cancer risk for BRCA1 and BRCA2 mutation carriers. Recent genome-wide association studies of breast cancer have identified eight additional breast cancer susceptibility loci: rs1011970 (9p21, CDKN2A/B), rs10995190 (ZNF365), rs704010 (ZMIZ1), rs2380205 (10p15), rs614367 (11q13), rs1292011 (12q24), rs10771399 (12p11 near PTHLH) and rs865686 (9q31.2).MethodsTo evaluate whether these single nucleotide polymorphisms (SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 39 publications
8
57
0
Order By: Relevance
“…From the prospective analysis, it would appear that the risk of breast cancer is significantly greater in women who test negative for familial BRCA2 compared with BRCA1 mutations. This is consistent with data showing much wider penetrance estimates for breast cancer in BRCA2 than in BRCA1 (5,(20)(21)(22)(23)(24)(25)(26), and the greater number of SNPs shown to modify BRCA2 risk (7,27). It is important to note that eight (six BRCA2) of the 21 cases have occurred after our previous report (4).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…From the prospective analysis, it would appear that the risk of breast cancer is significantly greater in women who test negative for familial BRCA2 compared with BRCA1 mutations. This is consistent with data showing much wider penetrance estimates for breast cancer in BRCA2 than in BRCA1 (5,(20)(21)(22)(23)(24)(25)(26), and the greater number of SNPs shown to modify BRCA2 risk (7,27). It is important to note that eight (six BRCA2) of the 21 cases have occurred after our previous report (4).…”
Section: Discussionsupporting
confidence: 77%
“…In the context of a family BRCA2 mutation, especially when there are multiple close relatives affected with early-onset breast cancer, specialists should advise that breast cancer risks may still be increased compared with the general population. The recent discovery of further genetic loci that alter penetrance predominantly in BRCA2 carriers (27) may facilitate additional testing for multiple SNPs to accurately predict whether those women negative for the familial BRCA2 mutation still have an increased genetic risk.…”
Section: Discussionmentioning
confidence: 99%
“…*Classical genome-wide statistical significance; # Nominal statistical significance, given the high prior probability of association based on evidence (at P < 5 × 10 −8 ) from other GWAS; † Genome-wide statistical significance in meta-analysis and HR estimate consistent in direction with findings for non-carriers; ‡ Statistical significance assessed in mutation carriers after adjustment for the top hit(s). a Antoniou et al (2010b); b Couch et al (2013); c Gaudet et al (2013); d Antoniou et al (2012) …”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…However, there is growing evidence that the increased cancer risk of BRCA1/2 mutation carriers can be modified by other genetic and non-genetic factors. In the past years, the international Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA) has identified a number of single-nucleotide polymorphisms (SNPs) that are associated with breast cancer risk [46,47,48,49,50,51,52,53]. Although the association of each single SNP is small, their combination may have a considerable effect on cancer risks, with potential impact on clinical decision-making [50].…”
Section: Cancer Risks Of Brca1/2 Mutation Carriersmentioning
confidence: 99%